Geographies of Love the Cultural Spaces of Romance in Chick- and Ladlit - Lenz, Christian 1983- (Cultural Studies, 2016)
»Geographies of Love« is the first study to explore the cultural lifeworlds of British, Australian and Indian chick- and ladlit characters. Offering unique case studies including Bridget Jones and Will Freeman (»About a Boy«), the book explores how love and romance are looked for, begun and conducted in specific spaces and places: the home and the office as well as shops, clubs and bars. This cross-disciplinary study provides scholars, students and keen readers with different points of access and easily-relatable situations so as to apprehend the complex phenomenon of cultural geographies within the field of literary studies